The impact of post-harvest storage on sweet corn aroma. (December 2022) - Yactayo-Chang, Jessica P.; Boehlein, Susan; Beiriger, Robert L.; Resende, Marcio F.R.; Bruton, Robert G.; Alborn, Hans T.; Romero, Maritza; Tracy, William F.; Block, Anna K.
Abstract: Fresh market sweet corn ( Zea mays L .) is a high sugar, high moisture vegetable that, due to its fast metabolic rate, is susceptible to rapid post-harvest decay at ambient temperatures. Immediate cooling and storage at low but not freezing temperatures are well established industry practices for maintaining post-harvest sugar content. Less is known about how post-harvest storage temperature impacts other important sweet corn consumer traits, such as aroma. In this study we measure the production and stability of the cooked sweet corn aroma compounds dimethyl sulfide, dimethyl disulfide, dimethyl trisulfide, 3-methyl furan, 3-methyl butanal and 2-methyl butanal. We reveal that these aroma compounds are also susceptible to post-harvest decay if sweet corn is stored at ambient rather than cool temperatures. Furthermore, the quantities and post-harvest decay rates of aroma volatiles vary among different sweet corn lines, indicating that sweet corn genetics can impact maintenance of post-harvest flavor. Graphical Abstract: Some aroma compunds found in cooked sweet corn. ga1 Highlights: Low temperature post-harvest storage maintains sugar content of sweet corn. Post-harvest storage also impacts the stability of cooked sweet corn aroma. Sweet corn varieties can have different aroma profiles and post-harvest stability. Genetic factors exist to improve the flavor related shelf life of sweet corn.